Manajemen Mutu terhadap Peningkatan Kualitas Lembaga Pendidikan Islam - Mila Mahmudah (Jurnal Keislaman, 2020)
Abstract: The term management has many meanings, management is directing / leading something of effort through planning, organizing, coordinating and controlling human resources and materials aimed at achieving predetermined goals. In the science of management there is the concept of problem solving that is placed in the workplace, namely the P-D-C-A approach as a process of solving problems with a continuous and systematic pattern. While management can also be defined as a process of organizing and utilizing the resources of the organization through the cooperation of members to achieve organizational goals effectively and efficiently. The practice of organizing education can be analogous to the production process in a company (industry). It's just that the products produced by educational institutions in the form of services. Therefore educational institutions can be said as service companies. From this perspective, the quality and quality of services (services) produced is a measure of the quality of an educational institution. Namely the extent of customer satisfaction with the services produced. What is meant by customers here are internal customers, namely teachers and other education personnel, and external customers, namely students and related parties outside the educational institution. Thus, schools are said to be of good quality if they are able to provide services according to or even exceed the expectations of teachers, employees, students, and other related parties such as parents, funders, the government or the world of work of users of graduates. Keywords: quality management, educational institutions